ANALYZING THE TRANSLATION OF INDONESIAN CULTURAL TERMS IN NOVEL ‘TARIAN BUMI’ TRANSLATED INTO ‘EARTH DANCE’ - Eka Murti (IJLECR (International Journal of Language Education and Cultural Review), 2021)
This research aims to obtain a deeper understanding of the Indonesian cultural terms in the novel Tarian Bumi and their translation into English, Earth Dance. This research focuses on the use of translation strategies, equivalences, errors, and factors affecting the errors. It uses a qualitative approach with the content analysis method. Both of the novels were read to find data. The collected data was divided, analyzed, and compared with their translation. The data analysis and explanation indicate that the strategy used in the translation of the cultural terms is a translation procedure amounted to 11 procedures, couplets and triplets are also used. The translation is oriented towards the source language because the translator often used procedures and equivalence oriented to the source language. The result of this research is also to look for translation errors of cultural terms and factors affecting the errors and to find how to solve them. It is caused by knowledge of the translator and different cultures. This research will give some benefits for those who are interested in studying the translation theory and other students who want to research Indonesian cultural terms translated into English.